Effects of tobacco control policies on smoking prevalence and tobacco-attributable deaths in Mexico: the SimSmoke model - Luz Myriam Reynales-Shigematsu; Nancy L. Fleischer; James F Thrasher; Yian Zhang; Rafael Meza; K. Michael Cummings; David T. Levy
OBJECTIVE: To examine how policies adopted in Mexico in response to the Framework Convention on Tobacco Control affected smoking prevalence and smoking-attributable deaths. METHODS: The SimSmoke simulation model of tobacco control policy is applied to Mexico. This discrete time, first-order Markov model uses data on population size, smoking rates and tobacco control policy for Mexico. It assesses, individually and jointly, the effects of seven types of policies: cigarette taxes, smoke-free air laws, mass media campaigns, advertising bans, warning labels, cessation treatment, and youth tobacco access policies. RESULTS: The Mexico SimSmoke model estimates that smoking rates have been reduced by about 30% as a result of policies implemented since 2002, and that the number of smoking-attributable deaths will have been reduced by about 826 000 by 2053. Increases in cigarette prices are responsible for over 60% of the reductions, but health warnings, smoke-free air laws, marketing restrictions and cessation treatments also play important roles. CONCLUSIONS: Mexico has shown steady progress towards reducing smoking prevalence in a short period of time, as have other Latin American countries, such as Brazil, Panama and Uruguay. Tobacco control policies play an important role in continued efforts to reduce tobacco use and associated deaths in Mexico.